1999
DOI: 10.1002/(sici)1097-0215(19990129)80:3<431::aid-ijc16>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the insulin-like growth factor-1 receptor promotes the survival of human keratinocytes following ultraviolet B irradiation

Abstract: The ultraviolet B (UVB) component of sunlight causes non‐melanoma skin cancers due to the damage it inflicts on genomic DNA. The response of epidermal keratinocytes to sunlight depends on the dose of UVB received and the severity of the damage to the DNA. Mild DNA damage typically induces DNA‐repair pathways and cell survival, while severe DNA damage provokes apoptosis. Primary human keratinocytes grown in serum‐free media respond in a similar manner to UVB irradiation. However, we observed that keratinocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 20 publications
4
106
0
Order By: Relevance
“…It also oVers escape mechanisms that allow the tumor to evade conventional treatment (Samani et al 2007). Studies propose that the IGF-1R may also play a role in protection of tumor cells from DNAdamaging agents such as chemotherapy, and ionizing radiation (Gil-Ad et al 1999;Gooch et al 1999;Jiang et al 1999;Kuhn et al 1999;Liu et al 1998b;Peters et al 1996). The beneWts of IGF-1R blockade in combination with radiotherapy have been widely documented (Criswell et al 2005), however, the focus of this review is the eVect of blocking IGF-1R on chemotherapy.…”
Section: Current Chemotherapy Approach To Cancersupporting
confidence: 92%
“…It also oVers escape mechanisms that allow the tumor to evade conventional treatment (Samani et al 2007). Studies propose that the IGF-1R may also play a role in protection of tumor cells from DNAdamaging agents such as chemotherapy, and ionizing radiation (Gil-Ad et al 1999;Gooch et al 1999;Jiang et al 1999;Kuhn et al 1999;Liu et al 1998b;Peters et al 1996). The beneWts of IGF-1R blockade in combination with radiotherapy have been widely documented (Criswell et al 2005), however, the focus of this review is the eVect of blocking IGF-1R on chemotherapy.…”
Section: Current Chemotherapy Approach To Cancersupporting
confidence: 92%
“…Normal human keratinocytes were isolated from neonatal foreskin tissue (Kuhn et al, 1999). Isolated keratinocytes were grown in EpiLife Complete media (Cascade Biologics, Portland, OR) supplemented with human keratinocyte growth supplement (Cascade Biologics) and 1000 U of penicillin-streptomycin (Roche Molecular Biochemicals, Indianapolis, IN).…”
Section: Cell Culturementioning
confidence: 99%
“…Fortunately, keratinocytes have developed many specific mechanisms to handle the unrelenting bombardment of carcinogenic insults. The in vitro-cultured keratinocyte model system has provided us with a wealth of information regarding how keratinocytes respond to UVB irradiation (Cotton and Spandau, 1997;Kumar et al, 1999;Kuhn et al, 1999;Qin et al, 2002;Zhang et al, 2002;Lewis et al, 2003Lewis et al, , 2006Chaturvedi et al, 2004;Lewis and Spandau, 2007a,b). In addition to the severity of UVB-induced DNA damage, events at the cell membrane of the keratinocyte, and their subsequent signal transduction cascades, critically control the fate of UVB-irradiated keratinocytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research found that UVB irradiation could give rise to cell apoptosis [8][9][10] , but it could also promote human epidermal cell growth under low dose irradiation and EGF existence [11] . The induced epidermal cells could resist UVB irradiation possibly because these cells received anti-apoptosis signals such as low dose irradiation promoted Rho B expression, EGF receptor activation induced AKT signal pathway which thereby promoted BAD phosphorylation and P53 downregulation [11][12][13] . Preliminary evidence in this study indicates that the induced epidermal cells acquired normal epidermal cell function to some extent.…”
Section: Discussionmentioning
confidence: 99%